PERTANGGUNGJAWABAN PERDATA PIHAK BANK X TERHADAP PENARIKAN TUNAI MELALUI TELLER TANPA SEPENGETAHUAN NASABAH DILIHAT DARI PERJANJIAN PADA SAAT PERMOHONAN PEMBUATAN KARTU ATM (AUTOMATIC TELLER MACHINE) - Prasantyo, Rafi Danendra; Kartika, Adhitya Widya (Universitas Ekasakti, 2023)
The modern banking system may appear safe and easy to use, but it still has its drawbacks. The public was shocked by the loss of a number of customer funds, even though the customer who owned the bank account did not believe that he was the one making the transaction. Customers' confidence in the safety of their bank deposits was shaken by this incident. The theft of bank customers' money shows a widening repertoire of criminal tactics. The purpose of this study is to analyze legal protection and the form of bank accountability to customers for cash withdrawals without the knowledge of customers through tellers in view of the agreement at the time of application for making an ATM card. This research method is included in the category of normative legal research. The results of this study state that in cases raised customers get legal protection for the use of problematic ATM card transactions. So if customers who experience problems in conducting ATM card transactions, customers can be guided by Law no. 10 of 1998 concerning Banking and Law no. 8 of 1999 concerning Consumer Protection